2007
DOI: 10.1590/s0080-62342007000300010
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos da comunicação da enfermeira com o deficiente auditivo

Abstract: Indivíduos com limitação auditiva têm seu processo comunicativo prejudicado. Procurou-se explorar aspectos da comunicação da enfermeira com os deficientes auditivos. Estudo descritivo-exploratório, realizado em hospitais de Fortaleza de maio a junho de 2004 mediante entrevistas abertas analisadas qualitativamente. As enfermeiras percebem que é difícil a comunicação com o deficiente auditivo, embora algumas tenham desempenho satisfatório. Nesse processo, algumas referem utilizar tanto a comunicação não verbal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
46

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 4 publications
0
20
0
46
Order By: Relevance
“…Nas relações comunicativas, a audição desempenha uma função importante na percepção do mundo das coisas e das relações sociais 1 . A ausência desse sentido é um dos fatores que desencadeiam distúrbios da comunicação, pois não ouvir dificulta a conversação por meio da linguagem oral, determinando a necessidade de se recorrer a variadas estratégias, visando a uma expressão e compreensão mais apropriadas da linguagem durante as trocas comunicativas, tanto pelos sujeitos surdos quanto pelos interlocutores ouvintes 2 .…”
Section: Introductionunclassified
“…Nas relações comunicativas, a audição desempenha uma função importante na percepção do mundo das coisas e das relações sociais 1 . A ausência desse sentido é um dos fatores que desencadeiam distúrbios da comunicação, pois não ouvir dificulta a conversação por meio da linguagem oral, determinando a necessidade de se recorrer a variadas estratégias, visando a uma expressão e compreensão mais apropriadas da linguagem durante as trocas comunicativas, tanto pelos sujeitos surdos quanto pelos interlocutores ouvintes 2 .…”
Section: Introductionunclassified
“…So were unsure when interacting with deaf people due to lack of skill in conveying information about your health. 18 In this context, a survey carried out on Paraiba found that among the 14 existing nursing courses, only eight offer Pounds as a component, these being optative private institutions. The adoption of the component Pounds in healthcare courses is of paramount importance in the training of professionals, as they will contribute to a full and fair service to all citizens.…”
mentioning
confidence: 99%
“…As proposed, professionals need to adapt their way of communicating and interacting, according to the patient, as each type of disability has its characteristics. Therefore, information is also needed on the patient's education level, so as to established the best form for this communication and relationship (10) .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding nursing care and assistance for disabled people, self-care activities are listed, such as: hygiene, nutrition, elimination, housework-related daily activities and childcare, among others (8) . Nursing research on the characteristics of communication between sensory disabled people and nurses should also be highlighted, with a view to improving care practice through the construction of verbal and non-verbal communication models (9)(10)(11) .…”
Section: Introductionmentioning
confidence: 99%